2020
DOI: 10.3390/jmse8030177
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Simulating Typhoon Waves Based on a Modified Holland Vortex Model

Abstract: A combination of the WAVEWATCH III (WW3) model and a modified Holland vortex model is developed and studied in the present work. The Holland 2010 model is modified with two improvements: the first is a new scaling parameter, bs, that is formulated with information about the maximum wind speed (vms) and the typhoon’s forward movement velocity (vt); the second is the introduction of an asymmetric typhoon structure. In order to convert the wind speed, as reconstructed by the modified Holland model, from 1-min ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The following points can be obtained from the figure : (1) M x and M y have values of the same order of magnitude, but M y plays a dominant role throughout the traveling process of the typhoon. (2) The bending moments of blades 2 and 3 are basically the same. Markedly, the rotor is under the aerodynamic imbalance condition.…”
Section: Loads Of the Blade Root And Tower Basementioning
confidence: 92%
See 2 more Smart Citations
“…The following points can be obtained from the figure : (1) M x and M y have values of the same order of magnitude, but M y plays a dominant role throughout the traveling process of the typhoon. (2) The bending moments of blades 2 and 3 are basically the same. Markedly, the rotor is under the aerodynamic imbalance condition.…”
Section: Loads Of the Blade Root And Tower Basementioning
confidence: 92%
“…On average, nine typhoons land on the southeast coast of China every year [1]. Typhoons are intensive ocean forces that can destroy coastal properties or offshore engineering structures, leading to significant economic losses [2]. Generally, typhooninduced waves are characterized by extreme heights [3,4], which pose a substantial threat to the stability and structural integrity of floating foundations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wave simulations were performed using WAVEWATCH III v5.16, developed by the National Centers for Environmental Prediction Environmental Modeling Center. This model has been validated in many previous studies and has been shown to realistically simulate the mean wave parameters and wave spectrum, especially under various TC conditions (Moon et al, 2003;Tolman et al, 2005;Fan et al, 2009;Montoya et al, 2013;Moon et al, 2016;Liu et al, 2017;Abdolali et al, 2020;Wang et al, 2020;Zieger et al, 2021). The spatial resolution of the current model was set to 1/12°x 1/12°(541 x 481), and the basic source term ST2 was used as the physics package (Tolman and Chalikov, 1996).…”
Section: Data and Design Of Numerical Experimentsmentioning
confidence: 99%
“…The wind field, as a driving factor, plays an important role in the simulation of typhoon waves. With the improvement of the accuracy requirements for typhoon waves in forecasting and post-forecasting modes, constructing a more accurate typhoon wind field model has become an important research topic (Rogers et al, 2007;Wang et al, 2020). This study introduces the Holland circular symmetric wind field model, superimposes the Holland wind field model and the moving wind field model to form a superimposed wind field model, and introduces an improved four-quadrant asymmetric wind field model based on the Holland model.…”
mentioning
confidence: 99%